Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Kosmetik Y.O.U di Panda Lovely Jombang - Fi Jannah, Hanifatur Rosyidah; Fadhli, Khotim (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This research aims to explore how price and product quality influence purchasing decisions for Y.O.U cosmetics at Panda Lovely Jombang. Given the rapid growth of Indonesia's cosmetics market, Y.O.U has emerged as a local brand offering quality products at competitive prices. Panda Lovely, with its numerous branches across Java Island, is one of Y.O.U’s primary distributors. The study adopts a quantitative approach using associative methods, with data collected through questionnaires from 100 Panda Lovely Jombang customers. Multiple linear regression analysis was employed to examine the relationship between independent variables (price and product quality) and the dependent variable (purchase decisions). The findings reveal that both price and product quality, individually and combined, significantly impact purchasing decisions. Key factors influencing consumer choices include affordability, the alignment of quality with expected benefits, and product durability. This research offers valuable insights for both Panda Lovely managers and Y.O.U producers to refine marketing strategies that cater to consumer needs and preferences.